Effect of local cooling on short-term, intense exercise - Kwon, Y. S.; Robergs, R. A.; Schneider, S. M. (The Journal of Strength and Conditioning Research, 2013)
The widespread belief that local cooling impairs short-term, strenuous exercise performance is controversial. Eighteen original investigations involving cooling before and intermittent cooling during short-term, intensive exercise are summarized in this review. Previous literature examining short-term intensive exercise and local cooling primarily has been limited to the effects on muscle performance immediately or within minutes following cold application. Most previous cooling studies used equal and longer than 10 minutes of pre-cooling, and found that cooling reduced strength, performance and endurance. Because short duration, high intensity exercise requires adequate warm-up to prepare for optimal performance, prolonged pre-cooling is not an effective method to prepare for this type of exercise. The literature related to the effect of acute local cooling immediately before short duration, high intensity isotonic exercise such as weight lifting is limited. However, local intermittent cooling during short-term, high intense exercise may provide possible beneficial effects; first, by pain reduction, caused by an "irritation effect" from hand thermal receptors which block pain sensation, or second, by a cooling effect, whereby stimulation of hand thermal receptors or a slight lowering of blood temperature might alter central fatigue.